Synthesis of 1,1-Bis-[2-hydroxy-3-(3-Aryl-Prop-2-en-1-one)-5-Methyl Phenyl Methane and their Dibromo Derivatives - Kinhikar, R.V.; Jamode, V.S. (Asian Journal of Chemistry, 2010)
New 1, 1-bis-[2-hydroxy-3-(3-aryl-prop-2-en-1-one )-5-methyl phenyl] methane, (4a-f), have been synthesised by the reaction of 1,1-bis-[2-hydroxy-3-acetyl-5-methyl phenyl] methane (3) with aromatic aldehydes in alkali medium and their dibromo derivatives, 1, 1-bis-[2-hydroxy-3-(2,3-dibromo-3-aryl-propan-1-one)-5-methyl phenyl] methane (5a-f) were synthesised by bromination of (4a-f) in acetic acid medium.